The Arabic influence on Northern Berber - Kossmann, Maarten G. (Studies in Semitic languages and linguistics, 2013)
"The Arabic Influence on Northern Berber provides an overview of the effects of language contact on a wide array of Berber languages spoken in the Maghrib. These languages have undergone important changes in their lexicon, phonology, morphology, and syntax as a result of over a thousand years of Arabic influence. The social situation of Berber-Arabic language contact is similar all over the region: Berber speakers introducing Arabic features into their language, with only little language shift going on. Moreover, the typological profile of the different Berber varieties is relatively homogenous. The comparison of contact-induced change in Berber therefore adds up to a study in typological variation of contact influence under very similar linguistic and social conditions."--Provided by publisher